Human Resource recruitment of Engineering Inspection Services of Bangladesh (EISB) - Shamme, Sharmin Sultana (BRAC University, 2015)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Master of Business Administration, 2015.